(untitled) (Olhar de Professor, 2022)
This paper is a part of the master’s thesis by the first author and it aims to understand the conceptions and policies of the teacher education in both Brazil and Honduras, taking as an example an undergraduate pedagogy course in each country. To achieve our purpose, we worked on a case study approach with qualitative bases for relying the development of the study on the documentary review and interviews with the current coordinators, as ways to collect the information. As a result, the interpretative analyses of the data show that the conception of teacher education legitimized in both countries is based on the principles of the technological paradigm. Despite this proximity, we conclude that its structuring is designed in different ways, especially in the policies and conceptions evoked.